A framework for reliability analysis in manufacturing plants - Mahadi Man (Fakulti Sains dan Teknologi, 2012)
With rapid advancement in plant manufacturing technologies, the equipments have become more complex. The complexity in plant equipments and the enormous amount of fault states that have to be handled and identified when they happen, make it very difficult for service engineers to find the roots and the symptoms of the problems correctly and promptly.